TRAINING ON APPLICATION OF MYCORRHIZAL BIOFERTILIZER IN EDAMAME PLANT AT PAMULIHAN VILLAGE, TANJUNGSARI DISTRICT, SUMEDANG REGENCY, WEST JAVA - Anne Nurbaity; Erni Suminar (Fakultas Pertanian, 2025)
Mycorrhizal biofertilizer is increasingly recognized as an eco-friendly soil amendment capable of improving nutrient uptake, plant resilience, and overall crop productivity. However, knowledge and utilization of mycorrhiza among smallholder farmers—especially housewives involved in home-scale farming—remain limited in many rural areas in Indonesia. This community service program aimed to enhance the knowledge, skills, and willingness of 20 housewives in Pamulihan Village, Tanjungsari District, Sumedang Regency, regarding the use of mycorrhizal biofertilizer for edamame cultivation. The training employed participatory learning methods, including lectures, demonstrations, hands-on practice, and discussions. Pre- and post-training assessments were conducted to evaluate changes in participants' understanding and readiness to adopt the technology. Results showed significant improvement across all indicators. Knowledge of the term “mycorrhiza” increased from 0% to 100%, ability to apply mycorrhiza increased from 0% to 100%, understanding of its benefits rose from 0% to 100%, and willingness to use mycorrhiza increased from 12.5% to 100%. Additionally, 68.75% of participants reported direct experience using mycorrhiza after the program, compared to none before. These results indicate that hands-on field-based training is highly effective in empowering rural communities—especially women—to adopt sustainable agricultural technologies. The program contributes to improved soil health, increased productivity potential for edamame, and enhanced environmental literacy in the village. The findings support the need for continued capacity building and community-based demonstrations to promote long-term adoption of biofertilizers.